2x-3/2x+1=3x+1/3x-1

Simple and best practice solution for 2x-3/2x+1=3x+1/3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3/2x+1=3x+1/3x-1 equation:



2x-3/2x+1=3x+1/3x-1
We move all terms to the left:
2x-3/2x+1-(3x+1/3x-1)=0
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
Domain of the equation: 3x-1)!=0
x∈R
We get rid of parentheses
2x-3/2x-3x-1/3x+1+1=0
We calculate fractions
2x-3x+(-9x)/6x^2+(-2x)/6x^2+1+1=0
We add all the numbers together, and all the variables
-1x+(-9x)/6x^2+(-2x)/6x^2+2=0
We multiply all the terms by the denominator
-1x*6x^2+(-9x)+(-2x)+2*6x^2=0
Wy multiply elements
-6x^3+12x^2+(-9x)+(-2x)=0
We get rid of parentheses
-6x^3+12x^2-9x-2x=0
We do not support expression: x^3

See similar equations:

| y/3+21=10 | | 18=3⋅x | | P=8x+3 | | x/5+25=15 | | x/2=31/2 | | 2x+5=-7+40 | | 5x+2=3X812 | | 8x-10x+40=0 | | g/2.9=10 | | 4x+4-4x-8=-15-10 | | -4k^2+64k+36=0 | | 8x=10x-40 | | 5x-2(3x±2)=1-2(4x+3) | | 6+x=−8 | | 41-4e=105 | | 3(12)+t=36 | | (500/q)+40-5q+q^2=0 | | -7+a=23 | | 10f+37=23 | | x*1.25=2 | | 4(5x-1)=3(4x+12 | | 14=x+22 | | 75y=5y | | 25+6n=91 | | 2(x-3)=5-(x+4) | | 2+11b=8b+5 | | 12x+9=7×+29 | | 3x+9=49−2x | | x+3+7-15=180 | | 2b/3*5=3 | | 0.9x-11975234.9=11770204 | | 2b/3.5=3 |

Equations solver categories